UJI IN VITRO DAN IN SILICO SENYAWA 5,7,2’,5’-TETRAHYDROXY FLAVAN-3-OL TERHADAP ENZIM ALPHA GLUCOSIDASE - Frengki Frengki; Deddi Prima; Fatma Sri Wahyuni; Daan Khambri; Henny Vanda; Noni Zakiah; Jamilah Abbas; Berna Elya (Faculty of Pharmacy, Universitas Muslim Indonesia, 2018)
Several of Calophyllums genus have been searched and proven as medicinal plants and Calophyllum macrophyllum is one of its genus. We have been isolated a compound from ethyl acetate fraction of the stem-bark. The compound was flavan-3-ol (5,7,2’,5’-tetrahydroxy flavan-3-ol). This research aimed to determine inhibition antidiabetic activity and affinity of its compound on α-glycosidase enzyme. In vitro antidiabetic effect shown by IC50 9.10 µg/ml and docking by Arguslab 4.01 shown by ΔG -10,24 kkal/mol as in silico test. The inhibition activity of flavan-3-ol against the α-glucosidase enzyme that is very strong shows its promising potential as a candidate for antidiabetic drugs.